Carbon mixture and manufacturing method thereof, electrode of all-solid-state battery and manufacturing method thereof

The carbon mixture with oxidation-treated carbon addresses sulfide-based solid electrolyte decomposition in all-solid-state batteries by increasing electrode density and maintaining capacity through specific surface area optimization.

JP2025047787APending Publication Date: 2025-04-03NIPPON CHEMI CON CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023156499
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

Sulfide-based solid electrolyte particles in all-solid-state batteries decompose when in contact with conventional conductive agents like carbon, leading to increased internal resistance and reduced capacity.

Method used

A carbon mixture is used as a conductive agent in the electrode, comprising oxidation-treated carbon that spreads like a paste when pressed, adhering to both electrode active material and sulfide-based solid electrolyte particles, with a specific external surface area of 50 to 130 m²/g, suppressing decomposition and enhancing electrode density.

Benefits of technology

The carbon mixture increases electrode active material content, improving electrode density and suppressing sulfide-based solid electrolyte particle decomposition, thereby maintaining battery capacity and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047787000001
    Figure 2025047787000001
  • Figure 2025047787000002
    Figure 2025047787000002
  • Figure 2025047787000003
    Figure 2025047787000003
Patent Text Reader

Abstract

To provide a carbon mixture to be used as a conductive agent in an electrode of an all-solid-state battery having a sulfide-based solid electrolyte layer, which can increase the content of electrode active material particles in the electrode to improve electrode density and also suppress decomposition of the sulfide-based solid electrolyte particles.SOLUTION: A carbon mixture includes an oxidation-treated carbon having the property of turning into a paste-like substance when subjected to pressure, and another conductive carbon having a higher electrical conductivity than that of the oxidation-treated carbon, and at least a portion of the oxidation-treated carbon spreads in a paste-like form and adheres to the surface of the other conductive carbon, and the carbon mixture has an external specific surface area in the range of 50 to 130 m2 / g.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon mixture to be used as a conductive agent in an electrode of an all-solid-state battery having a sulfide-based solid electrolyte layer, and a method for producing the same. The present invention also relates to an electrode of an all-solid-state battery containing the carbon mixture, and a method for producing the same. [Background technology]

[0002] All-solid-state batteries, which use a solid electrolyte instead of a liquid electrolyte, have excellent performance such as high energy density, high power density, high safety, and long life, and are therefore devices that are being widely considered for use in a variety of applications, such as for installation in electric vehicles, for smoothing the amount of power generated in power generation systems that utilize natural energy such as solar power generation and wind power generation, and for use as power sources for portable electronic devices such as mobile phones and portable personal computers.

[0003] This all-solid-state battery has, as essential components, a solid electrolyte layer and a pair of electrodes (positive and negative electrodes) facing each other via the solid electrolyte layer. The electrodes contain electrode active material particles that exhibit capacitance through a Faraday reaction involving the transfer of electrons with ions in the solid electrolyte, and solid electrolyte particles for forming an ion conduction path between the solid electrolyte layer and the electrode active material particles. When the electrode active material particles have low conductivity, the electrodes further contain a conductive agent for ensuring an electronic conduction path between the electrode active material particles and the electrode current collector. Conductive carbon is generally used as the conductive agent, and this conductive carbon not only ensures an electronic conduction path but also acts as a matrix for absorbing expansion and contraction accompanying the reaction of the electrode active material particles.

[0004] However, if the content of the solid electrolyte particles and conductive carbon in the electrode is reduced to the minimum amount that can ensure the ion conduction path and the electron conduction path, and the content of the electrode active material particles is increased, the energy density of the all-solid-state battery can be improved. Among the solid electrolyte particles, the sulfide-based solid electrolyte particles have high ion conductivity and flexibility compared to the oxide-based solid electrolyte particles, and even with a small amount of solid electrolyte particles, they can maintain good contact with the electrode active material particles and achieve charge transfer, so they are suitable for the purpose of improving the energy density. In addition, if the electrode active material particles expand and contract due to a reaction, the contact with the solid electrolyte particles is loosened, the charge transfer is inhibited, and the charge-discharge cycle life may be shortened, but the flexibility of the sulfide-based solid electrolyte particles is also useful for absorbing the expansion and contraction caused by the reaction of the electrode active material particles. Regarding conductive carbon, the applicant has proposed a method of increasing the content of electrode active material by using oxidized carbon, which has the property of spreading into a paste-like shape when subjected to pressure, as a conductive agent for electrodes, which can be obtained by subjecting a conductive carbon raw material to a strong oxidation treatment (for example, Patent Document 1 (WO2015 / 133586), Patent Document 2 (JP 2016-096125 A), Patent Document 3 (JP 2022-035788 A)). Here, "paste-like" means a state in which the grain boundaries of the primary carbon particles are not observed in an SEM photograph taken at a magnification of 25,000 times, and non-particulate amorphous carbon is connected.

[0005] Even when pressure is applied to conductive carbons such as carbon black, natural graphite, and carbon nanotubes, which are used as conductive agents in conventional electrodes, the particle shape of the carbon is maintained, making it difficult to increase the amount of active material per unit volume by reducing the distance between the active material particles, and high electrode density cannot be obtained. However, when these conductive carbons are subjected to an oxidation treatment, they are oxidized from the surface of the particles, and hydroxyl groups, carboxyl groups, carbonyl groups, ether bonds, etc. are introduced into the carbon, and the conjugated double bonds of the carbon are oxidized to form carbon single bonds, and carbon-carbon bonds are partially broken. By further increasing the intensity of the oxidation treatment, it is possible to obtain oxidized carbon that has the property of spreading like a paste when pressure is applied.

[0006] The oxidation-treated carbon, which has the property of spreading like a paste when subjected to this pressure, is characterized in that it easily adheres to the surface of the electrode active material particles, and when pressure is applied, it is compressed together and spreads like a paste, and is not easily broken apart. Therefore, when this oxidation-treated carbon and the electrode active material particles are mixed to obtain a mixture, the oxidation-treated carbon adheres to the surface of the active material particles during the mixing process, covering the surface, and improving the dispersibility of the active material particles. If the pressure applied to the oxidation-treated carbon during the production of the mixture is large, at least a part of the oxidation-treated carbon spreads like a paste and partially covers the surface of the active material particles. Then, when pressure is applied to the mixture during the process of producing the electrode, the oxidation-treated carbon further spreads like a paste, covering the surface of the electrode active material particles while densifying and the active material particles approach each other. Therefore, the amount of electrode active material per unit volume in the electrode can be increased to obtain a high electrode density.

[0007] Patent Document 1 shows that when conductive carbon having voids such as porous carbon powder, Ketjen Black, carbon nanofibers, and carbon nanotubes is used as a carbon raw material and oxidized, oxidized carbon having a property of spreading like a paste when pressure is applied can be easily obtained because it is easily oxidized. Figure 2 of this document shows the relationship between the electrode density and the content of the hydrophilic portion in the oxidized carbon obtained from an experiment in which oxidized carbon obtained by subjecting Ketjen Black to oxidation treatments of different strengths, particles of LiFePO4 as an electrode active material, polyvinylidene fluoride as a binder, and N-methylpyrrolidone as a solvent are thoroughly kneaded to form a slurry, which is then applied to an aluminum foil, dried, and then rolled to obtain an electrode. The meaning of the "hydrophilic portion" of the oxidized carbon and the method for calculating the content of the hydrophilic portion will be described later.

[0008] 2 of Patent Document 1 shows that when the intensity of the oxidation treatment is increased so that the content of the hydrophilic portion exceeds 8 mass% of the entire oxidized carbon, the density of the electrode manufactured using the obtained oxidized carbon begins to increase, when the content of the hydrophilic portion exceeds 9 mass% of the entire oxidized carbon, the electrode density begins to increase rapidly, and when the content of the hydrophilic portion exceeds 10 mass% of the entire oxidized carbon, an extremely high electrode density is obtained. This increase in electrode density corresponds to the fact that as the intensity of the oxidation treatment is increased, the oxidized carbon is given the property of spreading like a paste when pressure is applied.

[0009] Patent Document 2 discloses a method of dry-mixing the oxidation-treated carbon having the property of spreading like a paste when subjected to pressure as disclosed in Patent Document 1 with another conductive carbon having a higher conductivity than that of the oxidation-treated carbon, thereby obtaining a carbon mixture in which at least a part of the oxidation-treated carbon is changed into a paste-like form and adheres to the surface of the other conductive carbon. In Examples 10 and 11 of this document, a carbon mixture is obtained by dry-mixing oxidation-treated carbon having the property of spreading like a paste when subjected to pressure, obtained by subjecting Ketjen black to oxidation treatment, with acetylene black as another conductive carbon, and the carbon mixture is mixed with LiNi as an electrode active material. 0.5 Mn 0.3 Co 0.2 It has been shown that when O2 particles, polyvinylidene fluoride as a binder, and N-methylpyrrolidone as a solvent are thoroughly mixed to form a slurry, and this slurry is applied to an aluminum foil, dried, and then rolled to obtain an electrode, a high electrode density can be obtained, and the DC internal resistance of a lithium ion secondary battery equipped with this electrode is lower than the DC internal resistance of a lithium ion secondary battery equipped with an electrode formed by separately using the above-mentioned oxidized carbon and acetylene black instead of the above-mentioned carbon mixture.

[0010] Patent Document 3 shows a method of heat-treating the carbon mixture disclosed in Patent Document 2 in a vacuum or a non-oxidizing atmosphere to reduce the amount of CO2 generated from the carbon mixture after heat treatment in the range of 25 to 200°C compared to the amount of CO2 generated from the carbon mixture before heat treatment in the range of 25 to 200°C. Examples 1 to 4 of this document show a carbon mixture obtained by dry-mixing oxidation-treated carbon, which has the property of spreading like a paste when subjected to pressure and is obtained by subjecting Ketjen black to oxidation treatment, with acetylene black as another conductive carbon, and then heat-treating this carbon mixture at temperatures of 200 to 900°C in a nitrogen atmosphere electric furnace, and then mixing the obtained carbon mixture with LiNi as an electrode active material. 0.5 Mn 0.3 Co 0.2It has been shown that when O2 particles, polyvinylidene fluoride as a binder, and N-methylpyrrolidone as a solvent are thoroughly mixed to form a slurry, and this slurry is then applied to aluminum foil, dried, and then rolled to obtain an electrode, the charge-discharge cycle stability of an electricity storage device equipped with this electrode when a high voltage is applied is improved.

[0011] When the carbon mixture having high conductivity disclosed in Patent Document 2 and Patent Document 3 is used as a conductive agent in the electrode of an all-solid-state battery, the oxidized carbon contained in the carbon mixture spreads in a paste-like form and densifies while covering the surface of the electrode active material particles, so that even a small amount of carbon can ensure the electron conduction path necessary for the operation of the all-solid-state battery, and it is expected that the content of the electrode active material particles in the electrode can be increased to improve the electrode density. If the content of the electrode active material particles is increased, the energy density of the all-solid-state battery can be increased, and if a high electrode density is obtained, the moving distance of the ions responsible for the exchange of electrons with the electrode active material particles can be shortened. In addition, since the flexible carbon spread in a paste-like form covers the surface of the electrode active material particles, it is expected that the expansion and contraction caused by the reaction of the electrode active material particles can be suitably absorbed. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] WO2015 / 133586 [Patent Document 2] JP 2016-096125 A [Patent Document 3] Patent Publication No. 2022-035788 [Patent Document 4] JP 2018-055926 A [Non-patent literature]

[0013] [Non-Patent Document 1] Ore Geology Reviews 70(2015)80-95 Summary of the Invention [Problem to be solved by the invention]

[0014] As described above, sulfide-based solid electrolyte particles have high ionic conductivity and flexibility compared to oxide-based solid electrolyte particles, but on the other hand, they have a problem of high electrochemical or chemical reactivity. To address the problem of the reaction between the positive electrode active material particles and the sulfide-based solid electrolyte particles, a technology has been proposed in which a reaction suppression layer is provided on the surface of the positive electrode active material particles, but the sulfide-based solid electrolyte particles are in contact not only with the positive electrode active material particles but also with carbon as a conductive agent. It has been pointed out that the sulfide-based solid electrolyte particles in contact with carbon decompose during use of the all-solid-state battery.

[0015] For example, Patent Document 4 (JP 2018-055926 A) describes a LiNi battery having a reaction suppression layer such as Li3PO4 in an all-solid-state battery. 0.5 Mn 1.5 Even when a positive electrode active material such as O4 is used, it has been shown that the sulfide-based solid electrolyte particles are decomposed upon contact with the carbon at a high potential, releasing sulfur components such as sulfur atoms, sulfur molecules, and sulfur radicals. These sulfur components pass through the reaction suppression layer and carbon and ultimately diffuse into the inside of the positive electrode active material particles (see Figure 5 in this document).

[0016] Therefore, the inventors of the present invention conducted an experiment in which sulfide-based solid electrolyte particles were mixed with a carbon mixture specifically shown in Patent Document 2 and Patent Document 3, the mixture was molded by applying pressure, and then a voltage was applied to the molded product to investigate the reactivity between the sulfide-based solid electrolyte particles and the carbon mixture. As a result, it was found that decomposition of the sulfide-based solid electrolyte particles occurred. The decomposition of the sulfide-based solid electrolyte particles increases the internal resistance of the all-solid-state battery, leading to a decrease in capacity, and therefore should be improved.

[0017] Therefore, an object of the present invention is to provide a carbon mixture to be used as a conductive agent in an electrode of an all-solid-state battery having a sulfide-based solid electrolyte layer, which can increase the content of electrode active material particles to improve electrode density, and can also suppress decomposition of the sulfide-based solid electrolyte particles. [Means for solving the problem]

[0018] As a result of intensive research, the inventors have found that the external specific surface area of ​​the carbon mixture is 50 to 130 m 2 / g, the above-mentioned requirements can be met, and the present invention has been arrived at. Accordingly, the present invention is a carbon mixture to be used as a conductive agent in an electrode of an all-solid-state battery having a sulfide-based solid electrolyte layer, which contains an oxidation-treated carbon having a property of turning into a paste-like substance when subjected to pressure, and another conductive carbon having a higher conductivity than that of the oxidation-treated carbon, in which at least a part of the oxidation-treated carbon spreads in a paste-like state and adheres to the surface of the other conductive carbon, and the external specific surface area of ​​the carbon mixture is 50 to 130 m 2 / g, wherein the value of the external specific surface area of ​​the carbon mixture means the value of the external specific surface area obtained by the T-plot method from the results of nitrogen adsorption measurement according to JIS Z8831-2:2010.

[0019] The external specific surface area of ​​the carbon mixture is 50m 2 When the ratio is less than 1 / g, it becomes difficult to obtain the effect of increasing the content of the electrode active material particles in the electrode and improving the electrode density, and the external specific surface area of ​​the carbon mixture becomes 130 m 2 If the specific surface area of ​​the carbon mixture exceeds 65 to 115 m / g, the effect of suppressing the decomposition of the sulfide-based solid electrolyte particles in contact with the carbon mixture becomes difficult to obtain. 2 / g range is preferred.

[0020] In the carbon mixture of the present invention, the oxidation-treated carbon contains a hydrophilic portion, and the content of the hydrophilic portion is preferably 10% by mass or more of the entire oxidation-treated carbon, because the property of the oxidation-treated carbon spreading like a paste when subjected to pressure becomes prominent. The "hydrophilic portion" of the oxidation-treated carbon has the following meaning. That is, 0.1 g of the oxidation-treated carbon is added to 20 mL of an aqueous ammonia solution of pH 11, ultrasonic irradiation is performed for 1 minute, and the resulting liquid is left for 5 hours to precipitate the solid phase portion. The portion that does not precipitate and is dispersed in the aqueous ammonia solution of pH 11 is the "hydrophilic portion". The content of the hydrophilic portion relative to the entire oxidation-treated carbon is determined by the following method. After the precipitation of the solid phase portion, the remaining portion after removing the supernatant liquid is dried, and the weight of the solid after drying is measured. The weight obtained by subtracting the weight of the solid after drying from the weight of the initial oxidation-treated carbon of 0.1 g is the weight of the "hydrophilic portion" dispersed in the aqueous ammonia solution of pH 11. The weight ratio of the "hydrophilic portion" to the initial weight of the oxidized carbon (0.1 g) is the content of the "hydrophilic portion" in the oxidized carbon.

[0021] The present invention also provides a method for producing the carbon mixture of the present invention, comprising the steps of: An oxidation step of obtaining an oxidation-treated carbon having a property of turning into a paste-like substance when subjected to pressure by subjecting a conductive carbon raw material to an oxidation treatment; The oxidized carbon obtained in the oxidation step is dry-mixed with another conductive carbon having a higher conductivity than that of the oxidized carbon, so that at least a part of the oxidized carbon spreads in a paste-like form and adheres to the surface of the other conductive carbon, and has a thickness of 50 to 130 mm. 2 / g, preferably 65 to 115 m 2 / g range, The present invention relates to a method for producing a carbon mixture, comprising the steps of:

[0022] The external specific surface area of ​​the carbon mixture varies depending on conditions such as the particle shape and mass ratio of the oxidized carbon and the other conductive carbon used in the mixing step, the pressure applied to the oxidized carbon and the other conductive carbon during mixing, and the mixing time. 2 / g, preferably 65 to 115 m 2 / g range, the above-mentioned effects of the present invention can be obtained. In the oxidation step, it is preferable to carry out the oxidation treatment so that the content of hydrophilic parts in the obtained oxidized carbon is 10 mass % or more of the entire oxidized carbon, because this makes the oxidized carbon have a remarkable property of spreading like a paste when subjected to pressure.

[0023] When the other conductive carbon is carbon black having an average primary particle size of 25 to 80 nm, the external specific surface area of ​​the carbon mixture in the mixing step is set to 50 to 130 m 2 / g, preferably 65 to 115 m 2 The oxidation-treated carbon may have the property of changing into a paste-like form when subjected to pressure. However, the carbon raw material used in the oxidation step satisfies the following conditions i), ii), and iii): i) Internal specific surface area is 30m 2 / g or less, preferably 1 to 25m 2 / g range, ii) the average primary particle size is 35 nm or less, preferably in the range of 10 to 34 nm; iii) the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum is 1.00 or less, preferably in the range of 0.93 to 0.99; It is preferable to use carbon that satisfies all of the above. Patent documents 1 to 3 show specific examples using Ketjen black from the viewpoint of ease of oxidation, but carbon that satisfies all of the above conditions i), ii), and iii) can be given the property of changing into a paste-like state when pressure is applied with the same intensity of oxidation treatment as that applied to Ketjen black. In addition, when an electrode is manufactured by a method in which a carbon mixture containing oxidized carbon derived from Ketjen black, an electrode mixture containing electrode active material particles and sulfide-based solid electrolyte particles is obtained by dry mixing, and then the process of mixing with a binder and a solvent to form a slurry is omitted, and pressure is applied directly to the electrode mixture, voids are generated in the electrode, and these voids prevent the electrode density from increasing, but it has been found that the generation of voids is suppressed when a carbon mixture containing oxidized carbon derived from carbon that satisfies all of the above conditions i), ii), and iii) is used for the above-mentioned electrode manufacturing method.

[0024] Regarding condition i), the value of the internal specific surface area of ​​the carbon raw material is calculated by subtracting the value of the external specific surface area by the T-plot method derived from the results of nitrogen adsorption measurement according to JIS Z8831-2:2010 from the value of the BET specific surface area derived from the results of nitrogen adsorption measurement according to JIS Z8830:2013, i.e., the value of the total specific surface area. 2 Ketjenblack has a total specific surface area of ​​approximately 650 m 2 As can be seen from this, the internal specific surface area is 30 m 2 / g or less, preferably 1 to 25m 2 / g means that the carbon particles have almost no pores. Regarding condition ii), the value of the average primary particle size is derived from an SEM photograph of the carbon raw material. Regarding condition iii), the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of the carbon raw material is selected as a measure of the crystallinity of the carbon raw material. Non-Patent Document 1 (Ore Geology Reviews 70 (2015) 80-95) states that in the Raman spectrum of a highly crystalline graphite structure, a peak intensity of 2700 cm -1 The S1 band is observed near 2900 cm when the graphite structure is disturbed. -1 The S1 band appears near the S2 band (see A and B in Figure 3 of this document). When the crystal structure is disturbed, the peak intensity of the S2 band increases relatively, so the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum can be effectively used as a measure of the crystallinity of the carbon raw material.

[0025] The method for producing a carbon mixture of the present invention essentially includes the oxidation step and the mixing step. Following the mixing step, the carbon mixture obtained in the mixing step is heat-treated in a vacuum or in a non-oxidizing atmosphere to reduce the amount of CO2 generated from the carbon mixture after the heat treatment in the range of 25 to 200°C compared to the amount of CO2 generated from the carbon mixture before the heat treatment in the range of 25 to 200°C. By carrying out the heat treatment step, the charge / discharge cycle stability of an all-solid-state battery equipped with an electrode using the obtained carbon mixture during high voltage application is improved, so that the operating voltage of the obtained all-solid-state battery can be expanded. Note that the heat treatment does not affect the property of the oxidation-treated carbon to turn into a paste when subjected to pressure, and the external specific surface area of ​​the carbon mixture is also almost unchanged before and after the heat treatment. Here, the "amount of CO2 generated from the carbon mixture in the range of 25 to 200°C" has the following meaning. An experiment is conducted to measure the amount of CO2 generated while heating 30 mg of the carbon mixture to be measured using a temperature programmed desorption photoionization mass spectrometry (TPD-PIMS) device under conditions of atmospheric pressure helium atmosphere (helium flow rate 300 mL / min), temperature range from room temperature to 1200°C, and heating rate of 20°C / min. The total amount (integral value) of CO2 generated in the temperature range of 25 to 200°C calculated from the obtained experimental results is the "amount of CO2 generated from the carbon mixture in the range of 25 to 200°C."

[0026] The present invention further relates to an electrode for an all-solid-state battery having a sulfide-based solid electrolyte layer, the electrode comprising electrode active material particles, sulfide-based solid electrolyte particles, and the carbon mixture of the present invention as a conductive agent, and characterized in that at least a part of the carbon derived from the oxidized carbon spread in a paste-like form is attached not only to the surface of the other conductive carbon but also to the surfaces of the electrode active material particles and the sulfide-based solid electrolyte particles. Since the content of the electrode active material particles in this electrode is high, an all-solid-state battery having a high energy density can be obtained. In addition, since the decomposition of the sulfide-based solid electrolyte particles in this electrode is suppressed, the decrease in capacity of the all-solid-state battery can be suppressed. When an electrode having high strength is particularly required, the electrode of the present invention may further contain a binder.

[0027] The electrode of the all-solid-state battery having the sulfide-based solid electrolyte layer of the present invention can be manufactured by a method in which a mixture for an electrode containing the carbon mixture, the electrode active material particles, and the sulfide-based solid electrolyte particles is obtained by dry mixing, and then pressure is applied directly to the mixture for an electrode, omitting the step of mixing the mixture with a binder and a solvent to form a slurry. Hereinafter, the method of applying pressure directly to the mixture for an electrode, omitting the step of forming a slurry after obtaining the mixture for an electrode by dry mixing, is referred to as a "dry process". In addition, the term "dry press" refers to the pressure application step in the dry process.

[0028] Therefore, the present invention also provides a method for producing an electrode for an all-solid-state battery having a sulfide-based solid electrolyte layer by a dry process, comprising the steps of: a dry mixing step of dry-mixing electrode active material particles, sulfide-based solid electrolyte particles, and the carbon mixture of the present invention as a conductive agent to obtain a mixture for an electrode in which carbon originating from the oxidation treatment carbon, at least a part of which has spread in a paste-like form, is attached not only to the surface of the separate conductive carbon but also to the surfaces of the electrode active material particles and the sulfide-based solid electrolyte particles; and a dry pressing step of forming an active material layer from the electrode mixture and applying pressure to the active material layer to obtain an electrode in which at least a part of the carbon derived from the oxidized carbon, which has spread in a paste-like form, further spreads in a paste-like form and becomes densified; In the present specification, the portion of the carbon mixture derived from the oxidation-treated carbon is referred to as "carbon derived from the oxidation-treated carbon."

[0029] In the dry mixing step, the electrode mixture may be obtained by dry-mixing the entire amount of the sulfide-based solid electrolyte particles used for the electrode mixture together with the electrode active material particles and the carbon mixture of the present invention. However, the electrode mixture may be obtained by dry-mixing the entire amount of the sulfide-based solid electrolyte particles together without dry-mixing the entire amount of the sulfide-based solid electrolyte particles. A first step of dry-mixing a portion of the sulfide-based solid electrolyte particles used for the electrode mixture with the carbon mixture; A second step of dry-mixing the mixture obtained in the first step with the electrode active material particles; and A third step of dry-mixing the mixture obtained in the second step with the remaining sulfide-based solid electrolyte particles to obtain a mixture for an electrode. It is preferable to carry out the dry mixing step by a method including the steps 1 to 3, followed by the dry pressing step. It has been found that the electrode density is increased by carrying out the dry mixing step including the steps 1 to 3, compared to the case where the entire amount of the solid electrolyte particles is dry mixed together with the electrode active material particles and the carbon mixture.

[0030] The carbon mixture of the present invention is preferably used for manufacturing an electrode by the dry process described above. It is also possible to obtain an electrode slurry by adding a binder and a solvent to the electrode mixture obtained in the dry mixing step described above, form an active material layer using this electrode slurry, and apply pressure to the active material layer to obtain an electrode in which at least a portion of the carbon derived from the oxidized carbon described above spreads in a paste-like form and becomes further spread in a paste-like form and densified. Effect of the Invention

[0031] When an electrode for an all-solid-state battery is obtained using the carbon mixture of the present invention, electrode active material particles, and sulfide-based solid electrolyte particles, the content of the electrode active material particles can be increased to improve the electrode density, and decomposition of the sulfide-based solid electrolyte particles can be suppressed. [Brief description of the drawings]

[0032] [Figure 1] FIG. 1 is a diagram illustrating an evaluation device for evaluating the reactivity between a carbon mixture and sulfide-based solid electrolyte particles. [Diagram 2] FIG. 2 is a diagram showing the results of evaluation of the reactivity between a carbon mixture and a sulfide-based solid electrolyte using the evaluation device of FIG. [Diagram 3] FIG. 1 shows the density of pellets produced by a dry process. [Figure 4] FIG. 2 shows the density of a coating produced through the formation of a slurry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] (A) Carbon mixture and its manufacturing method The carbon mixture of the present invention to be used as a conductive agent in an electrode of an all-solid-state battery having a sulfide-based solid electrolyte layer contains an oxidation-treated carbon having a property of turning into a paste-like substance when subjected to pressure, and another conductive carbon having a higher conductivity than that of the oxidation-treated carbon, and at least a part of the oxidation-treated carbon spreads in a paste-like state and adheres to the surface of the other conductive carbon. 2 / g. The carbon mixture has an external specific surface area of ​​50 m 2 When the ratio is less than 1 / g, it becomes difficult to obtain the effect of increasing the content of the electrode active material particles in the electrode and improving the electrode density, and the external specific surface area of ​​the carbon mixture becomes 130 m 2If the specific surface area of ​​the carbon mixture exceeds 65 to 115 m / g, the effect of suppressing the decomposition of the sulfide-based solid electrolyte particles in contact with the carbon mixture becomes difficult to obtain. 2 / g range is preferred.

[0034] This carbon mixture is An oxidation step of obtaining an oxidation-treated carbon having a property of turning into a paste-like substance when subjected to pressure by subjecting a conductive carbon raw material to an oxidation treatment; The oxidized carbon obtained in the oxidation step is dry-mixed with another conductive carbon having a higher conductivity than that of the oxidized carbon, so that at least a part of the oxidized carbon spreads in a paste-like form and adheres to the surface of the other conductive carbon, and has a thickness of 50 to 130 mm. 2 / g, preferably 65 to 115 m 2 / g range, Each step will be described below.

[0035] (A-1) Oxidation stage In the oxidation stage, the conductive carbon raw material is oxidized until it is given the property of turning into a paste when pressure is applied. The carbon raw material used can be any conductive carbon used as a conductive agent for electrodes of conventional all-solid-state batteries, such as carbon blacks such as Ketjen black, acetylene black, furnace black, and channel black, fullerenes, carbon nanotubes, carbon nanofibers, graphene, amorphous carbon, carbon fibers, natural graphite, artificial graphite, graphitized Ketjen black, mesoporous carbon, and vapor-grown carbon fibers, without any particular limitation.

[0036] The carbon raw material is preferably conductive carbon having voids such as porous carbon powder, Ketjen black, carbon nanofibers and carbon nanotubes, particularly Ketjen black, because it is easy to oxidize. However, even carbon with almost no pores can be easily oxidized under the following conditions i), ii) and iii). i) Internal specific surface area is 30m 2 / g or less, preferably 1 to 25m 2 / g range, ii) the average primary particle size is 35 nm or less, preferably in the range of 10 to 34 nm; iii) the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum is 1.00 or less, preferably in the range of 0.93 to 0.99; Carbon that satisfies all of the above can be given the property of turning into a paste when subjected to pressure, with the same oxidation strength as that applied to Ketjen Black. In addition, when a carbon mixture containing oxidized carbon derived from Ketjen Black is used to manufacture an electrode by a dry process, voids are generated in the electrode, and these voids prevent the electrode density from increasing. However, it has been found that the generation of voids is suppressed when a carbon mixture containing oxidized carbon derived from carbon that satisfies all of the above conditions i), ii), and iii) is used to manufacture an electrode by a dry process instead of the oxidized carbon derived from Ketjen Black. Carbon that satisfies the above conditions i), ii), and iii) and is used as a carbon raw material can be selected from, for example, commercially available carbon blacks. Two or more types of carbon may be mixed and used as long as they satisfy all of the above conditions i), ii), and iii).

[0037] To oxidize the carbon raw material, a known oxidation method can be used without any particular limitation. For example, oxidized carbon can be obtained by treating the carbon raw material in an acid or hydrogen peroxide solution. As the acid, nitric acid, a nitric acid-sulfuric acid mixture, an aqueous hypochlorous acid solution, etc. can be used. In addition, oxidized carbon can be obtained by heating the carbon raw material in an oxygen-containing atmosphere, water vapor, or carbon dioxide. Furthermore, oxidized carbon can be obtained by mixing the carbon raw material with an alkali metal hydroxide, heating it in an oxygen-containing atmosphere, and removing the alkali metal by washing with water, etc. In addition, oxidized carbon can be obtained by subjecting the carbon raw material to plasma treatment, ultraviolet light irradiation, corona discharge treatment, glow discharge treatment, treatment with ozone water or ozone gas, or oxygen bubbling treatment in water in an oxygen-containing atmosphere.

[0038] When carbon raw material is subjected to oxidation treatment, the surface of the carbon particles is oxidized, hydroxyl groups, carboxyl groups, and ether bonds are introduced into the carbon, and the conjugated double bonds of the carbon are oxidized to generate carbon single bonds, and carbon-carbon bonds are partially cut, resulting in the generation of hydrophilic parts on the particle surface. By increasing the intensity of the oxidation treatment, the proportion of hydrophilic parts in the carbon particles increases, and it is possible to obtain oxidation-treated carbon that has the property of spreading like a paste when subjected to pressure. The content of hydrophilic parts in the oxidation-treated carbon is preferably 10% by mass or more of the entire oxidation-treated carbon. When subjected to pressure, such oxidation-treated carbon is easily compressed as a whole to spread like a paste and easily densified.

[0039] Oxidized carbon containing 10% or more by mass of hydrophilic moieties is (a1) treating a carbon raw material having voids or a carbon raw material satisfying all of the above conditions i), ii) and iii) with an acid; (b1) mixing the product after the acid treatment with a transition metal compound; (c1) grinding the mixture to cause a mechanochemical reaction; (d1) heating the product after the mechanochemical reaction in a non-oxidizing atmosphere; and (e1) removing the transition metal compound and / or its reaction product from the product after heating; The electrochemical cell can be suitably obtained by a first production method including the steps of:

[0040] In step (a1), the carbon raw material is immersed in acid and left to stand. Ultrasonic waves may be applied during this immersion. The acid may be an acid normally used in the oxidation treatment of carbon, such as nitric acid, a mixture of nitric acid and sulfuric acid, or an aqueous solution of hypochlorous acid. The immersion time depends on the concentration of the acid and the amount of the carbon raw material to be treated, but is generally in the range of 5 minutes to 5 hours. After the acid treatment, the carbon is thoroughly washed with water and dried, and then mixed with a transition metal compound in step (b1).

[0041] In step (b1), the transition metal compound added to the carbon after the acid treatment can be an inorganic metal salt such as a halide, nitrate, sulfate, or carbonate of a transition metal, or an organic metal salt such as a formate, acetate, oxalate, methoxide, ethoxide, or isopropoxide, or a mixture thereof. These compounds can be used alone or in combination of two or more. Compounds containing different transition metals can be mixed and used in a predetermined amount. In addition, as long as they do not adversely affect the reaction, a compound other than the transition metal compound, for example, an alkali metal compound, can be added together. In the present invention, since the carbon mixture containing the oxidation-treated carbon is mixed with the electrode active material particles and the sulfide-based solid electrolyte particles in the production of the electrode of the all-solid-state battery, it is preferable to add a compound of an element constituting the electrode active material or the sulfide-based solid electrolyte to the carbon after the acid treatment, since it is possible to prevent the inclusion of elements that may become impurities.

[0042] In step (c1), the mixture obtained in step (b1) is pulverized to cause a mechanochemical reaction. Examples of pulverizers for this reaction include a Raikai mill, a ball mill, a bead mill, a rod mill, a roller mill, an agitator mill, a planetary mill, a vibration mill, a hybridizer, a mechanochemical composite device, and a jet mill. The pulverization time depends on the pulverizer used and the amount of carbon to be treated, and is not strictly limited, but is generally in the range of 5 minutes to 3 hours. Step (d1) is performed in a non-oxidizing atmosphere such as a nitrogen atmosphere or an argon atmosphere. The heating temperature and heating time are appropriately selected depending on the transition metal compound used. In the subsequent step (e1), the transition metal compound and / or its reaction product are removed from the product after heating by means of dissolving it in an acid, etc., and then the product is thoroughly washed and dried to obtain an oxidized carbon.

[0043] In the first manufacturing method, in the step (c1), the transition metal compound acts to promote the oxidation of the carbon raw material by a mechanochemical reaction, and the oxidation of the carbon raw material proceeds rapidly. As a result, an oxidized carbon containing 10 mass % or more of hydrophilic parts in total is obtained.

[0044] The oxidized carbon containing 10% by mass or more of a hydrophilic portion is also (a2) mixing a carbon raw material having voids or a carbon raw material satisfying all of the above conditions i), ii) and iii) with a transition metal compound; (b2) heating the resulting mixture in an oxidizing atmosphere; and (c2) removing the transition metal compound and / or its reaction product from the product after heating. The second production method can be suitably obtained by the second production method comprising the steps of:

[0045] In step (a2), the transition metal compound added to the carbon raw material may be an inorganic metal salt such as a transition metal halide, nitrate, sulfate, or carbonate, an organic metal salt such as a formate, acetate, oxalate, methoxide, ethoxide, or isopropoxide, or a mixture thereof. These compounds may be used alone or in combination of two or more. Compounds containing different metals may be mixed and used in a predetermined amount. In addition, as long as they do not adversely affect the reaction, a compound other than the transition metal compound, for example, an alkali metal compound, may be added together. In the present invention, since the carbon mixture containing the oxidized carbon is mixed with the electrode active material particles and the sulfide-based solid electrolyte particles in the production of the electrode of the all-solid-state battery, it is preferable to add a compound of an element constituting the electrode active material or the sulfide-based solid electrolyte to the carbon raw material, since it is possible to prevent the inclusion of elements that may become impurities.

[0046] Step (b2) is carried out in an oxygen-containing atmosphere, for example, air, at a temperature at which the carbon is partially but not completely lost, preferably at a temperature of 200 to 350° C. In the subsequent step (c2), the transition metal compound and / or its reaction product is removed from the product after heating by means of dissolving it in an acid or the like, and then the product is thoroughly washed and dried to obtain oxidized carbon.

[0047] In the second production method, in the step (b2), the transition metal compound acts as a catalyst for oxidizing the carbon raw material, and the oxidation of the carbon raw material proceeds rapidly, resulting in the production of oxidized carbon containing 10 mass % or more of hydrophilic portions as a whole.

[0048] It is also possible to promote the oxidation of a carbon raw material having voids or a carbon raw material that satisfies all of the above conditions i), ii) and iii) by a method other than the first manufacturing method and the second manufacturing method.

[0049] (A-2) Mixing stage In the mixing step, the oxidized carbon obtained in the oxidation step is dry-mixed with another conductive carbon having a higher conductivity than that of the oxidized carbon, either as is or after being subjected to a pulverization treatment to homogenize the particle size, etc., as necessary. There are no particular limitations on the method of pulverization as necessary, and the pulverization may be performed by hand mixing using a mortar, or may be performed using a known mixing device such as a mortar, ball mill, bead mill, rod mill, roller mill, stirring mill, planetary mill, vibration mill, hybridizer, mechanochemical composite device, jet mill, or rotation / revolution mixer.

[0050] Examples of the other conductive carbon include carbon blacks such as ketjen black, acetylene black, furnace black, and channel black, which are used for electrodes of conventional all-solid-state batteries, fullerenes, carbon nanotubes, carbon nanofibers, graphene, amorphous carbon, carbon fibers, natural graphite, artificial graphite, graphitized ketjen black, mesoporous carbon, and vapor-phase carbon fibers. There is no particular limitation on the method of dry mixing of the oxidation-treated carbon and the other conductive carbon, and the mixture may be mixed by hand using a mortar, or may be mixed using a known mixing device such as a Raikai device, a ball mill, a bead mill, a rod mill, a roller mill, a stirring mill, a planetary mill, a vibration mill, a hybridizer, a mechanochemical composite device, a jet mill, or a rotation / revolution mixer.

[0051] Since the oxidation treated carbon has the property of spreading like a paste when subjected to pressure, during the process of dry mixing with the other conductive carbon in the mixing stage, the pressure applied to the oxidation treated carbon causes at least a part of the oxidation treated carbon to spread like a paste and adhere to the surface of the other conductive carbon. As this adhesion progresses, the external specific surface area of ​​the carbon mixture changes. The external specific surface area of ​​the resulting carbon mixture changes depending on conditions such as the particle shape and mass ratio of the oxidation treated carbon and the other conductive carbon used in the mixing stage, the pressure applied to the oxidation treated carbon and the other conductive carbon during mixing, and the mixing time. In the present invention, however, the external specific surface area of ​​the resulting carbon mixture is 50 to 130 m.2 / g, preferably 65 to 115 m 2 The dry mixing is performed so that at least a part of the oxidation-treated carbon spreads in a paste-like form and adheres to the surface of the other conductive carbon and the dry mixing time is 50 to 130 m. 2 / g, preferably 65 to 115 m 2 There is no strict restriction as long as a carbon mixture having an external specific surface area in the range of 1 / g is obtained, but it is generally in the range of 10 minutes to 1 hour.

[0052] When the other conductive carbon is carbon black having an average primary particle size of 25 to 80 nm, the external specific surface area of ​​the carbon mixture in the mixing step is set to 50 to 130 m 2 / g, preferably 65 to 115 m 2 / g range. In addition, if the conductivity of the other conductive carbon is 15 S / cm or more, an electrode having high conductivity can be obtained, which is preferable. The mass ratio of the oxidation-treated carbon to the other conductive carbon is generally in the range of 9:1 to 1:9.

[0053] In the case where charge / discharge cycle stability at high voltage application is required for the all-solid-state battery, the above mixing step is followed by: A heat treatment step in which the carbon mixture obtained in the mixing step is heat-treated in a vacuum or a non-oxidizing atmosphere, thereby reducing the amount of CO2 generated from the carbon mixture after the heat treatment in the range of 25 to 200°C compared to the amount of CO2 generated from the carbon mixture before the heat treatment in the range of 25 to 200°C. The external specific surface area of ​​the carbon mixture hardly changes before and after the heat treatment.

[0054] The charge-discharge cycle stability of an all-solid-state battery when a high voltage is applied tends to decrease if the number of substituents on the surface of the oxidation-treated carbon constituting the carbon mixture is large. However, it has been found that when the carbon mixture is heat-treated in a vacuum or in a non-oxidizing atmosphere, the amount of CO2 generated in the range of 25 to 200°C, which is mainly caused by the detachment from the carboxyl group on the surface of the oxidation-treated carbon, can be greatly reduced, and accordingly, improved charge-discharge cycle stability can be obtained in a charge-discharge cycle test when a high voltage is applied (see Patent Document 3). Moreover, the property of the oxidation-treated carbon contained in the carbon mixture before the heat treatment, which spreads like a paste when subjected to pressure, is maintained in the oxidation-treated carbon contained in the carbon mixture after the heat treatment, so this heat treatment does not affect the density of the electrodes of the all-solid-state battery.

[0055] The non-oxidizing atmosphere for the heat treatment may be composed of an inert gas such as nitrogen or argon, a reducing gas such as hydrogen or carbon monoxide, or a mixed gas of an inert gas and a reducing gas. The temperature and time of the heat treatment vary depending on the amount of the carbon mixture to be treated and the type of the heat treatment atmosphere. For example, when the heat treatment atmosphere is a nitrogen atmosphere, the treatment conditions can be 2 to 8 hours at a temperature of 200°C or more and less than 500°C, or 0.5 to 2 hours at a temperature of 500°C or more and 900°C or less.

[0056] (B) Electrodes and their manufacturing methods The carbon mixture of the present invention is used as a conductive agent for electrodes of an all-solid-state battery having a sulfide-based solid electrolyte layer, and at least one of the positive electrode and the negative electrode in the all-solid-state battery is manufactured using the carbon mixture of the present invention. Examples of sulfide-based solid electrolytes constituting the solid electrolyte layer in the all-solid-state battery include argyrodite-type solid electrolytes such as Li6PS5X (X=Cl, Br, I), Li 3.25 Ge 0.25 P 0.75Examples of such solid electrolytes include thiolisicone-type solid electrolytes such as S4, and glass-based solid electrolytes such as Li2S-Y (Y = P2S5, SiS2, GeS2, B2S3), LiI-Li2S-Y (Y = P2S5, SiS2, GeS2, B2S3), Li3PO4-Li2S-Y (Y = P2S5, SiS2, GeS2, B2S3), and Li4SiO4-Li2S-Y (Y = P2S5, SiS2, GeS2, B2S3).

[0057] The electrode manufactured using the carbon mixture of the present invention contains, as essential components, electrode active material particles that exhibit capacitance through a Faraday reaction involving the transfer of electrons with ions in a solid electrolyte, solid electrolyte particles for forming an ion conduction path between a solid electrolyte layer and the electrode active material particles, and the carbon mixture of the present invention for securing an electronic conduction path between the electrode active material particles and a current collector of the electrode. In this electrode, at least a part of the carbon derived from the oxidized carbon of the carbon mixture of the present invention spreads in a paste-like form and adheres not only to the surface of the separate conductive carbon but also to the surfaces of the electrode active material particles and the solid electrolyte particles.

[0058] As the electrode active materials for the positive and negative electrodes, electrode active materials used in conventional all-solid-state batteries can be used without any particular limitation. The electrode active material may be a single compound or a mixture of two or more compounds. Examples of the positive electrode active material include layered rock salt type LiMO2, layered Li2MnO3-LiMO2 solid solution, and spinel type LiM2O4 (wherein M means Mn, Fe, Co, Ni, or a combination thereof). Specific examples of these include LiCoO2, LiNiO2, LiNi 4 / 5 Co 1 / 5 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 1 / 2 Mn 1 / 2 O2, LiFeO2, LiMnO2, Li2MnO3-LiCoO2, Li2MnO3-LiNiO2, Li2MnO3-LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li2MnO3-LiNi1 / 2 Mn 1 / 2 O2, Li2MnO3-LiNi 1 / 2 Mn 1 / 2 O2-LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiMn2O4, LiMn 3 / 2 Ni 1 / 2 O4. Sulfur and Li2S, TiS2, MoS2, FeS2, VS2, Cr 1 / 2 V 1 / 2 Sulfides such as S2, selenides such as NbSe3, VSe2, NbSe3, Cr2O5, Cr3O8, VO2, V3O8, V2O5, V6O 13 In addition to oxides such as LiNi 0.8 Co 0.15 Al 0.05 O2, LiVOPO4, LiV3O5, LiV3O8, MoV2O8, Li2FeSiO4, Li2MnSiO4, LiFePO4, LiFe 1 / 2 Mn 1 / 2 Examples of the negative electrode active material include oxides such as Fe2O3, MnO, MnO2, Mn2O3, Mn3O4, CoO, Co3O4, NiO, Ni2O3, TiO, TiO2, SnO, SnO2, SiO2, RuO2, WO, WO2, and ZnO; metals such as Sn, Si, Al, and Zn; LiVO2, Li3VO4, and Li4Ti5O 12 Complex oxides such as Li 2.6 Co 0.4 Nitrides such as N, Ge3N4, Zn3N2, and Cu3N.

[0059] There is no limitation on the shape or particle size of the electrode active material particles, but the average particle size is preferably more than 2 μm and 25 μm or less. The electrode active material particles having such a relatively large particle size improve the electrode density by themselves, and in the electrode manufacturing process described below, the pressing force of the electrode active material particles promotes the gelatinization of the oxidized carbon. The surface of the electrode active material may be provided with a reaction suppression layer for suppressing the reaction with the sulfide-based solid electrolyte. Examples of compounds for constituting the reaction suppression layer include LiNbO3, Li3PO4, Li3BO3, Li4SiO4, Li4GeO4, LiTiO3, and LiZrO3. The thickness of the reaction suppression layer is selected so as not to inhibit the electrode reaction, and is generally several nm or less.

[0060] The sulfide-based solid electrolytes for the positive and negative electrodes are selected to be compatible with the sulfide-based solid electrolyte layer in the all-solid-state battery. 3.25 Ge 0.25 P 0.75 Examples of such solid electrolytes include thiolisicone-type solid electrolytes such as S4, and glass-based solid electrolytes such as Li2S-Y (Y = P2S5, SiS2, GeS2, B2S3), LiI-Li2S-Y (Y = P2S5, SiS2, GeS2, B2S3), Li3PO4-Li2S-Y (Y = P2S5, SiS2, GeS2, B2S3), and Li4SiO4-Li2S-Y (Y = P2S5, SiS2, GeS2, B2S3).

[0061] From the viewpoint of improving the energy density of the all-solid-state battery, the mass ratio of the electrode active material particles to the sulfide-based solid electrolyte particles is preferably in the range of 9:1 to 6:4, and the mass ratio of the total amount of the electrode active material particles and the sulfide-based solid electrolyte particles to the carbon mixture is preferably in the range of 90:10 to 99.5:0.5, more preferably in the range of 95:5 to 99:1. If the amount of the carbon mixture is less than the above range, the conductivity of the obtained electrode is insufficient, and the adhesion rate of the carbon mixture to the surface of the electrode active material particles tends to decrease. If the amount of the carbon mixture is more than the above range, the electrode density decreases, and the energy density of the all-solid-state battery tends to decrease.

[0062] The electrode of an all-solid-state battery having a sulfide-based solid electrolyte layer produced using the carbon mixture of the present invention is a dry mixing step of dry-mixing electrode active material particles, sulfide-based solid electrolyte particles, and the carbon mixture to obtain an electrode mixture in which carbon originating from the oxidation treatment carbon, at least a part of which has spread in a paste-like form, is attached not only to the surface of the separate conductive carbon but also to the surfaces of the electrode active material particles and the sulfide-based solid electrolyte particles; and a dry pressing step of forming an active material layer from the electrode mixture and applying pressure to the active material layer to obtain an electrode in which at least a portion of the carbon derived from the oxidized carbon, which has spread in a paste-like form, further spreads in a paste-like form and becomes densified; The present invention is produced by a method comprising the steps of:

[0063] There is no particular limitation on the order of mixing the electrode active material particles, the sulfide-based solid electrolyte particles, and the carbon mixture in the dry mixing step, and all of them may be mixed at the same time. Also, in the dry mixing step, the electrode mixture may be obtained by dry-mixing the entire amount of the sulfide-based solid electrolyte particles used for the electrode mixture together with the electrode active material particles and the carbon mixture of the present invention. However, the dry mixing step may be performed without dry-mixing the entire amount of the sulfide-based solid electrolyte particles together. A first step of dry-mixing a portion of the sulfide-based solid electrolyte particles used for the electrode mixture with the carbon mixture; A second step of dry-mixing the mixture obtained in the first step with electrode active material particles; and A third step of dry-mixing the mixture obtained in the second step with the remaining sulfide-based solid electrolyte particles to obtain a mixture for an electrode. It is preferable to carry out the dry mixing step by a method including the steps 1 to 3, followed by the dry pressing step. It has been found that when the dry mixing step including the steps 1 to 3 is carried out, the electrode density is increased compared to when the entire amount of the sulfide-based solid electrolyte particles is dry-mixed together with the electrode active material particles and the carbon mixture.

[0064] The method of dry mixing in the dry mixing step is not particularly limited, including the case where the dry mixing is performed by the above-mentioned first to third steps, and may be performed by hand mixing using a mortar, or may be performed using a known mixing device such as a mortar, a ball mill, a bead mill, a rod mill, a roller mill, an agitation mill, a planetary mill, a vibration mill, a hybridizer, a mechanochemical composite device, a jet mill, a rotation / revolution mixer, etc. There is no strict limit to the dry mixing time, as long as an electrode mixture is obtained in which at least a part of the carbon derived from the oxidized carbon in the carbon mixture is spread in a paste-like form and adheres not only to the surface of the other conductive carbon but also to the surface of the electrode active material particles and the surface of the sulfide-based solid electrolyte particles.

[0065] The dry pressing step following the dry mixing step can be carried out by forming an active material layer by laminating the obtained electrode mixture on a current collector by a known method such as electrostatic screen printing, and applying pressure to the active material layer. The electrode mixture may be introduced into a predetermined frame, and then molded by applying pressure, and the molded product may be pressed onto a current collector to carry out the dry pressing step. As the current collector, conductive materials such as platinum, gold, nickel, aluminum, titanium, steel, and carbon can be used. The shape of the current collector may be a film, foil, plate, or net shape. The pressure range in the dry pressing is generally 10 to 1500 MPa, preferably 50 to 1000 MPa. There is no particular limit to the temperature of the dry pressing process, and the process may be carried out at room temperature or under heating conditions.

[0066] When pressure is applied to the active material layer obtained from the electrode mixture in the dry pressing process, the oxidized carbon, at least a part of which has been changed to a paste-like state, spreads further and densifies while covering the surfaces of the electrode active material particles and the surfaces of the sulfide-based solid electrolyte particles, and the electrode active material particles approach each other. Therefore, the content of the electrode active material particles in the electrode can be increased to improve the electrode density, and therefore the energy density of the all-solid-state battery can be improved, and the migration distance of ions responsible for the exchange of electrons with the electrode active material particles can be shortened. In addition, the decomposition of the sulfide-based solid electrolyte particles is suppressed, so that the decrease in capacity of the all-solid-state battery can be suppressed.

[0067] The carbon mixture of the present invention is preferably used for manufacturing an electrode by the dry process described above. It is also possible to obtain an electrode slurry by adding a binder and a solvent to the electrode mixture obtained in the dry mixing step described above, form an active material layer using this electrode slurry, and apply pressure to the active material layer to obtain an electrode in which at least a portion of the carbon derived from the oxidized carbon described above spreads in a paste-like form and becomes further spread in a paste-like form and densified.

[0068] As the binder for obtaining the electrode slurry, known binders such as polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinyl fluoride, and carboxymethyl cellulose can be used without any particular limitation, and as the solvent, a solvent that does not adversely affect each component constituting the electrode, such as N-methylpyrrolidone or butyl acetate, can be used without any particular limitation. As long as each component constituting the electrode is mixed uniformly, there is no particular limitation on the amount of the solvent. The binder may be used in a form dissolved in a solvent. There is no particular limitation on the method of wet mixing for obtaining the electrode slurry, and it may be performed by hand mixing using a mortar, or may be performed using known mixing devices such as a Raikai device, a ball mill, a bead mill, a rod mill, a roller mill, a stirring mill, a planetary mill, a vibration mill, a hybridizer, a mechanochemical composite device, a jet mill, and a rotation / revolution mixer.

[0069] The obtained electrode slurry is applied onto a current collector to form an active material layer, and the active material layer is dried as necessary, and then pressure is applied to the active material layer to obtain an electrode. As the current collector, conductive materials such as platinum, gold, nickel, aluminum, titanium, steel, and carbon can be used. The shape of the current collector can be a film, a foil, a plate, a mesh, or the like. The active material layer can be dried by removing the solvent under reduced pressure and heating as necessary. The pressure range is generally 10 to 1500 MPa, and preferably 50 to 1000 MPa. There is no particular limit to the temperature when applying pressure to the active material layer, and the treatment can be performed at room temperature or under heated conditions.

[0070] When pressure is applied to the active material layer obtained from the electrode slurry, the oxidized carbon, at least a part of which has been changed to a paste-like state, spreads further and densifies while covering the surfaces of the electrode active material particles and the surfaces of the sulfide-based solid electrolyte particles, and the electrode active material particles approach each other. Therefore, the content of the electrode active material particles in the electrode can be increased to improve the electrode density, and therefore the energy density of the all-solid-state battery can be improved and the migration distance of ions responsible for the exchange of electrons with the electrode active material particles can be shortened. In addition, the decomposition of the sulfide-based solid electrolyte particles is suppressed, so that the decrease in capacity of the all-solid-state battery can be suppressed.

[0071] In addition to the above-mentioned electrode active material particles, sulfide-based solid electrolyte particles, the carbon mixture of the present invention as a conductive agent, and the binder and solvent used as necessary, the electrode of the all-solid-state battery of the present invention may contain other additives as long as they do not adversely affect the present invention. Examples of such additives include ferroelectric materials that have the effect of disturbing an electric field, such as BaTiO3, CaZrO3, SrBi2Ta2O9, and BiFeO3. EXAMPLES

[0072] The present invention will be described with reference to the following examples, but the present invention is not limited to the following examples.

[0073] (1) Manufacturing of oxidized carbon Manufacturing Example 1 As a carbon raw material, the total specific surface area is 270m 2 / g, and the external specific surface area is 264m 2 / g, and the internal specific surface area obtained from these values ​​is 6m 2 Carbon black with a molecular weight of 1.01g / g, an average primary particle size of 12nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of 0.965 was used. 10g of this carbon raw material was added to 300mL of 60% nitric acid, and the resulting liquid was irradiated with ultrasonic waves for 10 minutes, and then filtered to recover the carbon. The recovered carbon was washed with water three times and dried to obtain acid-treated carbon. 0.5g of this acid-treated carbon, 1.98g of Fe(CH3COO)2, 0.77g of Li(CH3COO), 1.10g of C6H8O7·H2O, 1.32g of CH3COOH, 1.31g of H3PO4, and 120mL of distilled water were mixed, and the resulting mixture was stirred with a stirrer for 1 hour, and then evaporated to dryness at 100°C in air to collect the mixture. The resulting mixture was then introduced into a vibration ball mill and pulverized at 20Hz for 10 minutes. The ground powder was heated in nitrogen at 700°C for 3 minutes to obtain a composite in which LiFePO4 was supported on carbon.

[0074] 1 g of the resulting composite was added to 100 mL of a 30% aqueous hydrochloric acid solution, and the resulting solution was irradiated with ultrasonic waves for 15 minutes to dissolve the LiFePO4 in the composite, and the remaining solid was filtered, washed with water, and dried. A part of the dried solid was heated to 900°C in air by TG analysis to measure the weight loss. The above-mentioned process of dissolving LiFePO4 in an aqueous hydrochloric acid solution, filtering, washing with water, and drying was repeated until it was confirmed that the weight loss was 100%, that is, no LiFePO4 remained, to obtain LiFePO4-free oxidation-treated carbon.

[0075] Manufacturing Example 2 Instead of the carbon raw material used in Production Example 1, a carbon fiber having a total specific surface area of ​​118 m 2 / g, and the external specific surface area is 111m 2 / g, and the internal specific surface area obtained from these values ​​is 7m 2 The procedure shown in Production Example 1 was repeated, except that carbon black having a molecular weight of 1.0 / g, an average primary particle size of 22 nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in a Raman spectrum of 0.977 was used as the carbon raw material.

[0076] Production Example 3 Instead of the carbon raw material used in Production Example 1, 2 / g, and the external specific surface area is 215m 2 / g, and the internal specific surface area obtained from these values ​​is 10m 2 The procedure shown in Production Example 1 was repeated, except that carbon black having a molecular weight of 1.0 / g, an average primary particle size of 25 nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in a Raman spectrum of 0.943 was used as the carbon raw material.

[0077] Production Example 4 Instead of the carbon raw material used in the manufacturing example, a carbon fiber with a total specific surface area of ​​59 m 2 / g, and the external specific surface area is 43m 2 / g, and the internal specific surface area obtained from these values ​​is 16m 2 The procedure shown in Production Example 1 was repeated, except that carbon black having a molecular weight of 1.0 / g, an average primary particle size of 31 nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in a Raman spectrum of 0.966 was used as the carbon raw material.

[0078] Reference manufacturing example In order to obtain a reference for the property of changing into a paste-like form when pressure is applied, the carbon raw material used in Production Example 1 was replaced with Ketjen Black EC300J (total specific surface area of ​​788 m2) shown in Patent Documents 2 and 3. 2 / g, and the external specific surface area is 139m 2 / g, and the internal specific surface area obtained from these values ​​is 647 m 2The procedure shown in Preparation Example 1 was repeated, except that 1,2-dichloroethane (1,2-dichloroethane) was used as the carbon source.

[0079] The content of hydrophilic moieties in the oxidation-treated carbon of Production Examples 1 to 4 and the Reference Production Example exceeded 10% by mass of the entire oxidation-treated carbon. Next, in order to confirm whether the oxidation-treated carbon has the property of turning into a paste when subjected to pressure, the following experiment was carried out. Two parts by mass of the oxidation-treated carbon of any of Production Examples 1 to 4 and the Reference Production Example, and LiNi 0.5 Mn 0.3 Co 0.2 96 parts by mass of O2 particles (average particle size 5 μm) and were introduced, and dry-mixed at 2000 rpm for 5 minutes, and then 2 parts by mass of N-methylpyrrolidone containing polyvinylidene fluoride were introduced and kneaded. The kneaded mixture obtained was applied to an aluminum foil and dried, and then SEM photographs of the dried product were taken to confirm whether the oxidized carbon had changed to a paste-like state. As a result, the oxidized carbon of Production Examples 1 to 4 no longer had a granular shape like the oxidized carbon of the Reference Production Example, and the oxidized carbon that had changed to a paste-like state was attached to the surface of the active material particles. Therefore, it was found that even if the carbon raw material had almost no pores, if the carbon raw material had a small average primary particle size and low crystallinity, the carbon raw material could be given the property of changing to a paste-like state when pressure was applied by the strength of the oxidation treatment equivalent to that applied to Ketjen Black.

[0080] (2) Preparation of carbon mixture and evaluation of reactivity between the carbon mixture and sulfide-based solid electrolyte particles Comparative Example 1 The oxidized carbon of Production Example 1 was introduced into a vibration ball mill and ground for 20 minutes at 10 Hz. The ground oxidized carbon and furnace black, another conductive carbon, with an average primary particle size of 22 nm were then introduced into the vibration ball mill in a mass ratio of 1:1 and dry mixed for 10 minutes at 20 Hz to obtain a mixture, which was then heat-treated in a nitrogen atmosphere at 400°C for 6 hours to obtain a carbon mixture. The external specific surface area of ​​the resulting carbon mixture was 169 m. 2 / g.

[0081] The reactivity of this carbon mixture with sulfide-based solid electrolyte particles was evaluated under the following conditions. The carbon mixture and Li6PS5Cl as sulfide-based solid electrolyte particles were introduced into a vibration ball mill in a mass ratio of 1:1, and dry-mixed at 20 Hz for 10 minutes to obtain a mixture for evaluation. The obtained mixture for evaluation was then placed in a cylindrical insulating fixture (inner circle area: 1 cm) of the evaluation device shown in FIG. 1. 2 ) as the working electrode, and a Li / Li was placed between the lower and upper metal jigs of this evaluation device. + A voltage of 4.4 V was applied to the capacitor, and the value of the current flowing was measured.

[0082] Example 1 The oxidized carbon of Production Example 1 was introduced into a vibration ball mill and ground for 20 minutes at 10 Hz. The ground oxidized carbon and furnace black, another conductive carbon, with an average primary particle size of 41 nm were then introduced into the vibration ball mill in a mass ratio of 1:1 and dry mixed for 10 minutes at 20 Hz to obtain a mixture, which was then heat-treated at 400°C for 6 hours in a nitrogen atmosphere to obtain a carbon mixture. The external specific surface area of ​​the resulting carbon mixture was 113 m. 2 The reactivity between the obtained carbon mixture and the sulfide-based solid electrolyte particles was evaluated according to the procedure shown in Comparative Example 1.

[0083] Example 2 The oxidized carbon of Production Example 2 was introduced into a vibration ball mill and ground for 20 minutes at 10 Hz. The ground oxidized carbon and furnace black, another conductive carbon, with an average primary particle size of 35 nm were then introduced into the vibration ball mill in a mass ratio of 1:1 and dry mixed for 10 minutes at 20 Hz to obtain a mixture, which was then heat-treated in a nitrogen atmosphere at 400°C for 6 hours to obtain a carbon mixture. The external specific surface area of ​​the resulting carbon mixture was 98 m 2 The reactivity between the obtained carbon mixture and the sulfide-based solid electrolyte particles was evaluated according to the procedure shown in Comparative Example 1.

[0084] Example 3 The oxidized carbon of Production Example 3 was introduced into a vibration ball mill and ground for 20 minutes at 10 Hz. The ground oxidized carbon and furnace black, another conductive carbon, with an average primary particle size of 42 nm were then introduced into the vibration ball mill in a mass ratio of 1:1 and dry mixed for 10 minutes at 20 Hz to obtain a mixture, which was then heat-treated in a nitrogen atmosphere at 400°C for 6 hours to obtain a carbon mixture. The external specific surface area of ​​the resulting carbon mixture was 83 m. 2 The reactivity between the obtained carbon mixture and the sulfide-based solid electrolyte particles was evaluated according to the procedure shown in Comparative Example 1.

[0085] Example 4 The oxidized carbon of Production Example 4 was introduced into a vibration ball mill and ground for 20 minutes at 10 Hz. The ground oxidized carbon and furnace black, another conductive carbon, with an average primary particle size of 42 nm were then introduced into the vibration ball mill in a mass ratio of 1:1 and dry mixed for 10 minutes at 20 Hz to obtain a mixture, which was then heat-treated at 400°C for 6 hours in a nitrogen atmosphere to obtain a carbon mixture. The external specific surface area of ​​the resulting carbon mixture was 69 m. 2The reactivity between the obtained carbon mixture and the sulfide-based solid electrolyte particles was evaluated according to the procedure shown in Comparative Example 1.

[0086] Comparative Example 2 The oxidized carbon of Production Example 1 was introduced into a vibration ball mill and ground for 20 minutes at 10 Hz. The ground oxidized carbon and furnace black, another conductive carbon, with an average primary particle size of 100 nm were then introduced into the vibration ball mill in a mass ratio of 1:1 and dry mixed for 10 minutes at 20 Hz to obtain a mixture, which was then heat-treated at 400°C for 6 hours in a nitrogen atmosphere to obtain a carbon mixture. The external specific surface area of ​​the resulting carbon mixture was 36 m. 2 The reactivity between the obtained carbon mixture and the sulfide-based solid electrolyte particles was evaluated according to the procedure shown in Comparative Example 1.

[0087] Example 5 The oxidized carbon of Production Example 1 was introduced into a vibration ball mill and ground for 20 minutes under conditions of 10 Hz. Next, the ground oxidized carbon and acetylene black, another conductive carbon, with an average primary particle size of 35 nm were introduced into the vibration ball mill in a mass ratio of 1:1 and dry mixed for 10 minutes at 20 Hz to obtain a mixture, which was then heat-treated in a nitrogen atmosphere at 400°C for 6 hours to obtain a carbon mixture. The external specific surface area of ​​the obtained carbon mixture was 97 m 2 The reactivity between the obtained carbon mixture and the sulfide-based solid electrolyte particles was evaluated according to the procedure shown in Comparative Example 1.

[0088] Fig. 2 is a diagram showing the relationship between the external specific surface area of ​​the carbon mixture and the current measured in the reactivity evaluation test. As the decomposition of the sulfide-based solid electrolyte particles in contact with the carbon mixture progresses, the detected current value increases, but Fig. 2 shows that as the external specific surface area of ​​the carbon mixture decreases, the detected current decreases. Note that the external specific surface area of ​​the carbon mixture containing the oxidized carbon of the reference production example shown in Patent Documents 2 and 3 instead of the oxidized carbon of Production Examples 1 to 4 was 150 m 2 / g, and the current value measured in the reactivity evaluation test was 0.068 mA. Therefore, in order to suppress the decomposition of the sulfide-based solid electrolyte particles in contact with the carbon mixture more than when the carbon mixtures shown in Patent Documents 2 and 3 are used, the external specific surface area of ​​the carbon mixture needs to be 130 m 2 It was found that it was necessary to reduce the concentration to less than / g.

[0089] (3) Electrode production and evaluation of electrode density Comparative Example 3 The carbon mixture in Comparative Example 1 (external specific surface area: 169 m) was placed in a mortar. 2 2 parts by mass of 75 mol% Li2S-25 mol% P2S5 particles as a solid electrolyte were added to the mixture, and dry-mixed for 5 minutes (first step). 0.5 Mn 0.3 Co 0.268 parts by mass of O2 particles (average particle size 5 μm) were introduced and dry mixed for 5 minutes (second step), and 15 parts by mass of 75 mol% Li2S-25 mol% P2S5 particles as a solid electrolyte were introduced and dry mixed for 5 minutes (third step) to obtain an electrode mixture. Next, in order to measure the density of the electrode produced by the dry process, a powder resistance measurement system (MCP-PD51, manufactured by Mitsubishi Chemical Analytical) was used to dry press 2.3 g of the obtained electrode mixture at a pressure of 63 MPa to produce a pellet (electrode), and the pellet density (electrode density) was calculated from the volume of the obtained pellet. In addition, polyvinylidene fluoride as a binder was added to the electrode mixture in the mortar in an amount such that the electrode mixture:binder was 98:2 in mass ratio, and the mixture was mixed, and an appropriate amount of butyl acetate as a solvent was added and mixed to produce an electrode slurry. This slurry was applied onto an aluminum foil and dried, and then a coating film was produced by performing roll pressing three times under a condition of 1 t / cm. The coating film density (electrode density) was calculated from the volume and weight of the obtained coating film.

[0090] Example 6 Instead of the carbon mixture in Comparative Example 1, the carbon mixture in Example 1 (external specific surface area: 113 m 2 The procedure given in Comparative Example 3 was repeated except that 100 g of 10 ...

[0091] Example 7 Instead of the carbon mixture in Comparative Example 1, the carbon mixture in Example 2 (external specific surface area: 98 m 2 The procedure given in Comparative Example 3 was repeated except that 100 g of 10 ...

[0092] Example 8 Instead of the carbon mixture in Comparative Example 1, the carbon mixture in Example 3 (external specific surface area: 83 m 2 The procedure given in Comparative Example 3 was repeated except that 100 g of 10 ...

[0093] Example 9 Instead of the carbon mixture in Comparative Example 1, the carbon mixture in Example 4 (external specific surface area: 69 m 2 The procedure given in Comparative Example 3 was repeated except that 100 g of 10 ...

[0094] Comparative Example 4 Instead of the carbon mixture in Comparative Example 1, the carbon mixture in Comparative Example 2 (external specific surface area: 36 m 2 The procedure given in Comparative Example 3 was repeated except that 100 g of 10 ...

[0095] Example 10 Instead of the carbon mixture in Comparative Example 1, the carbon mixture in Example 5 (external specific surface area: 97 m 2 The procedure given in Comparative Example 3 was repeated except that 100 g of 10 ...

[0096] FIG. 3 is a diagram showing the relationship between the external specific surface area of ​​the carbon mixture and the pellet density (electrode density) of the pellets (electrodes) manufactured by the dry process. By comparing FIG. 2 with FIG. 3, it can be seen that the current measured in the reactivity evaluation test and the pellet density are in a proportional relationship. In addition, when only acetylene black having an average primary particle diameter of 35 nm was used instead of the carbon mixture in Example 5, the pellet density was 2.7 g / cc, and only a slight improvement in pellet density was observed in the pellets in Comparative Example 4. Taking into consideration the results shown in FIG. 3 and the results shown in FIG. 2, in order to achieve both an improvement in pellet density corresponding to an increase in the content of electrode active material particles and suppression of decomposition of sulfide-based solid electrolyte particles, the external specific surface area of ​​the carbon mixture needs to be set to 50 to 130 m. 2 It was found that the range of .mu.m / g was required.

[0097] FIG. 4 is a diagram showing the relationship between the external specific surface area of ​​the carbon mixture and the coating film density (electrode density) of the coating film (electrode) obtained using the electrode slurry, and the same results as those in FIG. 3 were obtained. When only acetylene black having an average primary particle diameter of 35 nm was used instead of the carbon mixture in Example 5, the coating film density was 2.6 g / cc, and only a slight improvement in the coating film density was observed in the pellets in Comparative Example 4. Therefore, even when an electrode is obtained using an electrode slurry, in order to achieve both an improvement in electrode density corresponding to an increase in the content of electrode active material particles and suppression of decomposition of sulfide-based solid electrolyte particles, it is necessary to increase the external specific surface area of ​​the carbon mixture to 50 to 130 m. 2 It was found that the range of .mu.m / g was required. [Industrial Applicability]

[0098] By using the carbon mixture of the present invention as a conductive agent in the electrodes of an all-solid-state battery having a sulfide-based solid electrolyte layer, it is possible to obtain an all-solid-state battery having a high energy density and suppressed capacity reduction.

Claims

1. A carbon mixture to be used as a conductive agent in an electrode of an all-solid-state battery having a sulfide-based solid electrolyte layer, the carbon mixture comprising: an oxidation-treated carbon having a property of turning into a paste-like substance when subjected to pressure; and another conductive carbon having a higher electrical conductivity than that of the oxidation-treated carbon, wherein at least a portion of the oxidation-treated carbon spreads in a paste-like state and adheres to a surface of the other conductive carbon, The external specific surface area of ​​the carbon mixture is 50 to 130 m 2 / g range of the carbon mixture.

2. The carbon mixture according to claim 1 , wherein the oxidation-treated carbon contains a hydrophilic portion, and the content of the hydrophilic portion is 10 mass % or more of the total oxidation-treated carbon.

3. A method for producing the carbon mixture according to claim 1, comprising the steps of: An oxidation step of obtaining an oxidation-treated carbon having a property of turning into a paste-like substance when subjected to pressure by subjecting a conductive carbon raw material to an oxidation treatment; The oxidized carbon obtained in the oxidation step is dry-mixed with another conductive carbon having a higher conductivity than that of the oxidized carbon, so that at least a part of the oxidized carbon spreads in a paste-like form and adheres to the surface of the other conductive carbon, and the mixture has a thickness of 50 to 130 mm. 2 1. A carbon mixture having an external specific surface area in the range of 1 / g. A method for producing a carbon mixture, comprising:

4. The method for producing a carbon mixture according to claim 3 , wherein in the oxidation step, the oxidation treatment is carried out so that the content of hydrophilic parts in the obtained oxidized carbon is 10 mass % or more of the total oxidized carbon.

5. The carbon raw material satisfies the following conditions i), ii) and iii): i) Internal specific surface area is 30 m 2 / g or less, ii) the average primary particle size is 35 nm or less; iii) the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in a Raman spectrum is 1.00 or less; The method for producing a carbon mixture according to claim 3 or 4, wherein the carbon satisfies all of the above requirements.

6. The method for producing a carbon mixture according to claim 3 or 4, wherein the other conductive carbon is carbon black having an average primary particle size of 25 to 80 nm.

7. The carbon mixture obtained in the mixing step is heat-treated in a vacuum or a non-oxidizing atmosphere, thereby reducing the amount of CO generated from the heat-treated carbon mixture in the range of 25 to 200°C. 2 The amount of CO generated from the carbon mixture before heat treatment at temperatures between 25 and 200°C 2 Reduce the amount by heat treatment The method for producing a carbon mixture according to claim 3 or 4, further comprising:

8. An electrode for an all-solid-state battery having a sulfide-based solid electrolyte layer, The present invention comprises an electrode active material particle, a sulfide-based solid electrolyte particle, and the carbon mixture according to claim 1 or 2 as a conductive agent, An electrode for an all-solid-state battery, characterized in that at least a portion of the carbon that originates from the oxidized carbon and spreads in a paste-like form adheres not only to the surface of the separate conductive carbon but also to the surfaces of the electrode active material particles and the surfaces of the sulfide-based solid electrolyte particles.

9. The electrode of claim 8 , wherein the electrode further comprises a binder.

10. A method for producing an electrode for an all-solid-state battery having a sulfide-based solid electrolyte layer, comprising the steps of: a dry mixing step of dry-mixing electrode active material particles, sulfide-based solid electrolyte particles, and a carbon mixture obtained by the manufacturing method according to claim 3 or 4 as a conductive agent, thereby obtaining a mixture for an electrode in which carbon originating from the oxidized carbon, at least a part of which has spread in a paste-like form, is attached not only to the surface of the separate conductive carbon but also to the surfaces of the electrode active material particles and the sulfide-based solid electrolyte particles; and a dry pressing step of forming an active material layer from the electrode mixture and applying pressure to the active material layer to obtain an electrode in which at least a part of the carbon derived from the oxidized carbon, which has spread in a paste-like form, further spreads in a paste-like form and becomes densified; A method for producing an electrode, comprising:

11. The dry mixing step comprises: A first step of dry-mixing a portion of the sulfide-based solid electrolyte particles used for the electrode mixture with the carbon mixture; A second step of dry-mixing the mixture obtained in the first step with the electrode active material particles; and A third step of dry-mixing the mixture obtained in the second step with the remaining sulfide-based solid electrolyte particles to obtain a mixture for an electrode. The method of claim 10, comprising:

Citation Information

Patent Citations

  • Electrode, method for producing the electrode, electricity storage device provided with the electrode, and conductive carbon mixture for electricity storage device electrode

    JP2016096125A

  • Sulfide solid battery

    JP2018055926A

  • Conductive carbon and production method thereof, production method of conductive carbon mixture containing the conductive carbon, and production method of electrode by use of the conductive carbon or conductive carbon mixture

    JP2022035788A

  • Conductive carbon, electrode material including said conductive carbon, and electrode using said electrode material

    WO2015133586A1